SMART GHG Mobile Application: A New Agricultural App for Tracking GHG Emissions and Low-Carbon Rice Production in Thailand’s Local Communities - Nittaya Cha-un; Sirintornthep Towprayoon; Amnat Chidthaisong; Kittipong Chaimanuskul; Suwapat Maiyarach; Panuwat Sangsuwan; Pichit Kiatsomporn (Chemistry Proceedings, 2022)
Rice fields and cultivation activities are sources of greenhouse gas (GHG) emissions. Therefore, quantification of the baseline emissions is necessary to discover and implement the appropriate mitigation options for the transition to low-carbon rice production in order to achieve the Sustainable Development Goals (SDGs) by 2030. This study aimed to track and estimate the baseline GHG emissions and the carbon footprint (C-footprint) from rice cultivation in three farmer communities in Thailand. The SMART GHG mobile application (SGA) was used to calculate the GHG emissions from many cultivation activities and calculate the C-footprint of paddy rice production. The field activity data were collected from 71 farmer households with 134 ha of harvested areas in Muang Chang (MJ) sub-district of Nan province, Suan Taeng (ST) sub-district of Suphan Buri province, and Na Kham (NK) sub-district of Nakorn Phanom province. The results from SGA showed that the total GHG emissions of MJ, ST and NK communities accounted for 7.5, 6.3 and 2.9 tCO2e ha−1, respectively. The mean of total GHG emissions from all communities accounted for 5.6 tCO2e ha−1. During the rice growing period with flooded fields, the emission of CH4 contributed to 83.4% of the total GHG emissions. Whereas, the cultivation activities of fertilization, field preparation, harvest, and residue burning shared small emissions of 5.4, 4.4, 3.8 and 2.0%, respectively. The SGA also reported the C-footprint of paddy yields by 1.77, 1.10 and 1.09 kgCO2e kg yield−1 in MJ, NK and ST, respectively. This study indicated that the SGA can effectively demonstrate and track the GHG emissions and C-footprint, which can be developed into a baseline emission and mitigation for low-carbon rice production. This is a challenge for agriculture and rural community development in Thailand.